A Proof of Concept for Blockchain-Based Microcredential Verification in Higher Education - Fadlan, Muhammad; Noviyantono, Endyk; Muhammad, Muhammad (International Journal of Advances in Data and Information Systems, 2026)
The risk of counterfeiting and inefficient verification processes poses challenges for the validation of additional microcredential in higher education institutions, where most verification mechanisms remain manual and depend on the issuing institution. To address this issue, a blockchain-based Proof of Concept will be developed to facilitate the verification process of these microcredential. This Research uses an experimental approach by building and testing a prototype system on a limited scale. The proposed solution utilizes blockchain technology with a hash-based verification approach, where only the digital representation of the microcredential is recorded in a smart contract deployed on an Ethereum based blockchain. The testing process for the developed prototype was conducted using microcredential datasets, both original and modified microcredential, as simulations of forgery. The results indicate that the developed blockchain-based system prototype can distinguish genuine from counterfeit microcredential. These findings demonstrate that blockchain-based verification mechanisms have the potential to reduce reliance on manual verification processes. However, this Research is still at the proof of concept stage on a limited scale, and its implementation in a real world environment still requires further testing.